Medication Fall Risk Score and Evaluation Tools: Cross-Cultural daptation for Use in Brazil - Eckert, Vitória Ceia Ramos; Millão, Luzia Fernandes; Urbanetto, Janete de Souza (O Mundo da Saúde, 2023)
Falls are a potential problem for all patients, especially as the risk increases in the hospital environment, regardless of the institution. Many factors may be associated with falls, including balance, which may be influenced by the use of medication. The application of an assessment scale for the risk of falls is one of the most used tools in Brazil and in the world, but it is also necessary to evaluate the medications the patient is using. The objective of this study is to carry out the cross-cultural adaptation and validation of the Medication Falls Risk Score and the Evaluation Tools for the Brazilian Portuguese language. Method: Methodological study for the cross-cultural adaptation and validation of the Medication Falls Risk Score and Evaluation Tools, using the protocol by Beaton et al. and performing the validation of the feasibility of both scales. The instruments obtained an average Content Validity Index (CVI) of 0.99, being considered valid. The validation of the feasibility of both instruments had favorable results, 65.2% of the participants found the tool easy to apply, and the average time taken to apply it was 13 minutes and 30 seconds. Among the difficulties encountered, the difficulty of recognizing the drugs in terms of their therapeutic class stands out, which justifies the difference between the time of application and the accuracy of the applied test. The tools were cross-culturally adapted to Brazilian Portuguese and demonstrated excellent agreement and practicality in healthcare settings. The approved scale and tools may serve as support for the identification, classification, and multidisciplinary care regarding the risk of falls in hospitalized patients, with the Morse Fall Scale - Brazilian version being an additional assessment.